Cuckoo search algorithm with different distribution strategy. (3rd June 2019) - Tang, Hengliang; Xue, Fei
Cuckoo search (CS) is a new meta-heuristic search algorithm based on the obligate nest parasitism of cuckoos and combining the characteristic flight of some birds and fruit flies. In order to study the influence of distribution strategy on cuckoo search algorithm, in the paper, introduces Cauchy distribution, Gaussian distribution, Uniform distribution and Levy distribution, analysis the performance of cuckoo search algorithm by the method of pair combination. In order to verify the effectiveness of the algorithm, 28 typical test functions proposed by CEC2013 were taken as examples for testing, and the experimental results showed the effectiveness of the algorithm. Simulation results show that the hybrid distribution of Levy distribution and Cauchy distribution can make the cuckoo search algorithm perform better.